On the role of sectoral and national components in the wage bargaining process - Christian Dreger; Hans-Eggert Reimers (Institute for the Study of Labor (IZA), 2010)
This paper provides an empirical analysis on the determination of wages at the sectoral level in main industrial economies. Nominal wages are bargained between labour unions and employers in imperfect competitive markets, where spillovers across sectors might occur. Using a principal component approach, sectoral wage growth rates are separated into common and idiosyncratic components. This defines the relative role of national and sector specific conditions in the wage determination process. The common component is highly relevant especially in continental Europe, and is more visible for manufacturing than for services sectors. It reflects national inflation and productivity growth, while labour market tightness is negligible. The weight of the macroeconomic environment has declined in recent years. Wage growth tends to be more in line with idiosyncratic conditions like sectoral productivity and prices, probably due to the ongoing globalization of markets.
Keywords: C22; C23; E24; 330; Sectoral wages; wage spillovers; common factors; Lohnverhandlungen; Lohnbildung; Sektorale Lohnstruktur; Spillover-Effekt; Hauptkomponentenanalyse; Schätzung; Vergleich; Deutschland; Frankreich; Italien; USA; Großbritannien